Veščine komuniciranja v inženirskem poklicu - Verdonik, Darinka (University of Maribor Press, 2021)
Communication Skills in Engineering Profession. The present teaching material is adapted for students of computer science and technical sciences in general. It addresses a range of communication topics and tries to illuminate various aspects of private, business and public communication, either from the perspective of text/speech production or comprehension. The topics are: (1) various forms of communication in the workplace with an emphasis on work meetings; (2) various forms of public speaking; (3) some basic theoretical concepts about communication and comprehension; (4) the miscommunication; (5) the importance of active listening; (6) nonverbal communication; (7) characteristics of professional writing; (8) politeness; (9) conflict management; (10) various aspects of persuasion.